Mitogen-Activated Protein Kinase Cascade in the Basolateral Nucleus of Amygdala Is Involved in Extinction of Fear-Potentiated Startle - Kwok‐Tung Lu; David L. Walker; Michael Davis (2001)
Previous results indicate that intra-amygdala infusions of NMDA receptor antagonists block the extinction of conditioned fear. Mitogen-activated protein kinase (MAPK) can be activated by NMDA receptor stimulation and is involved in excitatory fear conditioning. Here, we evaluate the role of MAPK within the basolateral amygdala in the extinction of conditioned fear. Rats received 10 light-shock pairings. After 24 hr, fear was assessed by eliciting the acoustic startle reflex in the presence of the conditioned stimulus (CS) (CS-noise trials) and also in its absence (noise-alone trials). Rats subsequently received an intra-amygdala or intrahippocampal infusion of either 20% DMSO or the MAPK inhibitor PD98059 (500 ng/side) followed 10 min later by 30 presentations of the light CS without shock (extinction training). After 24 hr, they were again tested for fear-potentiated startle. PD98059 infusions into the basolateral amygdala but not the hippocampus significantly reduced extinction, which was otherwise evident in DMSO-infused rats. Control experiments indicated that the effect of intra-amygdala PD98059 could not be attributed to lasting damage to the amygdala or to state dependency. These results suggest that a MAPK-dependent signaling cascade within or very near the basolateral amygdala plays an important role in the extinction of conditioned fear.